Technological opportunities, absorptive capacities, and innovation - Wolfgang Becker; Jürgen Peters (Universität Augsburg, Institut für Volkswirtschaftslehre, 2000)
The aim of this paper is to analyze the effects of technological opportunities on the innovation activities of firms, depending on their absorptive capacities. The importance and impacts of the ability of firms to use external knowledge sources were inquired especially for external knowledge stemming from scientific research. Using a simple theoretic model, different innovation effects were empirically outlined for the German manufacturing industry for the first time. On the innovation input side, the effects of science-related technological opportunities in combination with absorptive capacities variables are stronger on the intensities as in the estimations without such proxies. Further, the innovation output of firms is positively influenced by the ability to adapt external knowledge efficiently. Firms in the German manufacturing industry with inhouse absorptive capacities and a high importance of scientific knowledge are characterized by higher sales shares of new and improved products and higher probabilities of patent registrations than other firms.
urn:nbn:de:bvb:384-opus4-276840
Keywords: O31; I20; L20; L60; 330; Technological Opportunities; Absorptive Capacities; Innovation; Scientific Knowledge